Mengembangkan Kemampuan Motorik Halus Anak Usia 4-5 Tahun Melalui Kegiatan Melukis Dengan Jari di TK Nikita PTPN V Bukit Selasih - Tri Rahma Karlina Sari; Sulistiyani Sulistiyani; Sulastri Sulastri (Jurnal Pendidikan Tuntas, 2023)
When these elements perform their respective roles in a positive interaction, meaning that one element is interrelated, mutually supporting, complementary with other elements to achieve a more perfect motor condition. Children with brain disorders appear less skilled in moving their bodies. Finger painting is a painting technique activity without any tools by applying paint to wet paper using the fingers of the hands done by the child to pour his imagination through paintings done by the fingers of the hands by the child. This finger painting technique is a painting technique without the use of tools. This research method uses classroom action research, which is a research method that occurs in the classroom during the interaction between teachers and students. The purpose of this classroom action research is to improve and improve the quality of learning and help empower teachers in solving problems in learning at school, and to improve and improve learning practices at school, as well as to increase the relevance of education, quality of education and efficiency in education management. Keywords; Finger painting, Fine motor skills, early childhood